The Method of Medical-Ecological Monitoring of Public Health and Environmentally Hazardous Areas - Oleh Yermishev (Kazimierz Wielki University, 2020)
The main subject of the study of the ecological and medical zoning method is the complex state of the autonomic nervous system (ANS) of the child's organism and the analysis of the processes affecting it. The ANS performs adaptational trophic function - the regulation of the metabolism regarding the conditions of the environment. The analysis of possible ecological problems of the territory and its degree of ecological disturbance can be made due to the received data set on the state of functional health of the children's population of a certain territory and the averaged information on the deviation of the autonomic nervous system. In order to assess the disturbance of the territory, the relative value of the breach of vegetative homeostasis, which is defined as a percentage, is of particular importance. Various organs and systems of the body are known to be associated with certain areas of the skin called acupuncture points. With the appearance of the smallest deviations in the systems of the body and organs, they react at the stage of functional disorders long before the occurrence of organic changes at the expense of meridional bonds. Measuring the electrosurgical resistance in certain acupuncture points you can detect changes in the body still at the stage of functional disorders. For researches, the method of "biogalvanization" of 24 symmetrical representative active functional zones (12 on the arms and 12 on the legs), which reflect the functional activity of the sympathetic and parasympathetic nervous system has been used. This allows to record changes in the activity of sites of the ANS and to obtain systematic data that are subject to further complex analysis. The given method is unique and allows to conduct ecological analysis of the territory with the help of the target group of organisms - a person; method is non-invasive and low-cost, which allows conducting surveys of different age and sex groups and obtaining data with a minimum statistical error.